(untitled) (Al-Academy, 2017)
Sound effects are considered to be a key element in children’s theatre, for it relays the context and amplifies its understandability, acceptability and its impact on the audience, so it’s a fundamental method in portraying the characters within the idea or the story, to produce the title and content with completeness in its relations that are associated with the rest of the fundamental elements represented in lighting, costumes, dialogue, decoration, etc. And this research included a set of subjects that are related to implementing the sound effects used in the Iraqi children’s theatre plays, chapter one included the problem and the need for studying this subject, as well as its importance and aim, and specifying the basic phrases within the title, as for chapter two it included the theoretical structure represented in the following elements: (Iraqi children’s theatre, sound effects) while chapter three included the research’s methodology which adopted the descriptive methodology in analyzing the research’s sample, then the researcher analyzed two samples from the research’s domain which was represented with (12) samples, chapter four included the conclusions and results as well as the recommendations and suggestions and finally the researcher ended the research with a list of references